Patrol Boat Strengthening Against a Collision with COLL Notation Based on Class Rules and Regulation in Indonesia – An Overview - Abid Paripurna Fuadi; Teguh Muttaqie; Andi Cahyo Prasetyo Tri Nugroho; Yudiawan Fajar Kusuma; Suherman Mukti; Mohammad Arif Kurniawan; Topan Firmandha; Muhammad Ismail (Mekanika)
Indonesian maritime security and law enforcement rely frequently on Patrol boats. However, collisions can occur during the operation, leading to potential loss of life, damage to the ship, and environmental harm. In preventing such incidents, the government needs to strengthen the patrol boats against collisions in accordance with class rules and regulations in Indonesia.The COLL notation is an additional notation for vessel collision protection, which specifies the required strength of the vessel's hull and structural components to minimize the risk of damage and reduce the consequences of a collision. This study highlights the key areas that require strengthening, including the vessel’s bow, stern, and hull, as well as the propulsion system that needs to be considered in the design stage. The addition of collision bulkheads, increasing the hull plating thickness, and reinforcing the engine mounts and shafting are also necessary to ensure the vessel's safety against collision. In conclusion, strengthening patrol boats against a collision with COLL notation based on class rules and regulations in Indonesia is one of the methods available that can be applied for the design stage to increase the level of operational safety of patrol boats.